Post-war political economics and the growth of Australian university research, c.1945-1965. Issue 1 (5th June 2017) - Forsyth, Hannah
Abstract : Purpose: The purpose of this paper is to consider the national and international political-economic environment in which Australian university research grew. It considers the implications of the growing significance of knowledge to the government and capital, looking past institutional developments to also historicise the systems that fed and were fed by the universities. Design/methodology/approach: The paper is based on the extensive archival research in the National Archives of Australia and the Australian War Memorial on the formation and funding of a wide range of research programmes in the immediate post-war period after the Second World War. These include the Australian Atomic Energy Commission, the NHMRC, the Commonwealth Scientific and Industrial Research Organisation, the Australian Pacific Territories Research Council, the Commonwealth Office of Education, the Universities Commission and the Murray review. This research was conducted under the Margaret George Award for emerging scholars for a project entitled "Knowledge, Nation and Democracy in Post-War Australia". Findings: After the Second World War, the Australian Government invested heavily in research: funding that continued to expand in subsequent decades. In the USA, similar government expenditure affected the trajectory of capitalist democracy for the remainder of the twentieth century, leading to a "military-industrial complex". The outcome in Australia looked quite different, though still connected to the structure and character of Australian political economics. Originality/value: The discussion of the spectacular growth of universities after the Second World War ordinarily rests on the growth in enrolments. This paper draws on a very large literature review as well as primary research to offer new insights into the connections between research and post-war political and economic development, which also explain university growth.